Rancang Bangun Aplikasi Input Data Analisa Tandan Untuk Pemilihan Pohon Induk di PT. Palma Inti Lestari (PT. PIL) - Marwa, Safni; Yola Utari, Anisa (Journal of Engineering Science and Technology Management, 2022)
The palm plantation is a major commodity in the Riau province where PT. Palma Inti Lestari (PT. PIL) take a role as a production unit of palm oil sprouts. Sprouts produced by PT. PIL have gone through the research and testing phase, first. The best quality sprouts come from the best quality parent tree. To get the parent tree with the best quality, then researched the palm oil fruit from different palm trees in one month. In determining the best quality parent tree, determined by lab officials through a series of data analysis. The data is oil content data, thin shell, big fruit, And that's a lot of credit. It replicates the data from this research as well (thousand). Right now, the research records are still manual, where data from the field is input to the computer using Microsoft Excel. Given the amount of research data that should be inserted one by one into the excel table, with a storage system done only by stand alone computer, causing a riot/probably an error in input data. As one solution resolves error in input data with resource state in the field, then an application is created to facilitate employees as operators in the input data of cluster analysis that will later be selected to make parent trees in producing quality sprouts. This data input application is designed using UML and built using VBA that supports Microsoft Access Applications